Internet Access Influences Community Clinic Portal Use - Alexa P?rez (Mary Ann Liebert, 2018)
Purpose: To assess whether individuals attending a community clinic had the necessary Internet access and experience to use the patient portal, while examining covariates of education, income, and self-perception of health with past and anticipated portal use. Methods: Adults attending an urban, community primary care clinic were invited to participate in a brief survey assessing current Internet access and use, past portal use, and anticipated future portal use. Survey responses were analyzed using descriptive and multivariate statistics. Results: One hundred fifteen participants ranging in age from 18 to 84 years (mean 42.1, standard deviation 17.1) completed the survey; 6 (5%) in Spanish. Thirty-five (30%) self-identified as Latino; 12 (10%) as Asian; and 20 (17%) as other. Almost 80% reported their health as good or better. Although 38% reported some college and 47% reported being college graduates, 60% reported household incomes were <$50,000. Most (87%) used the Internet for >1 year. Fewer than half (42%) had past portal use, with significant differences associated with weekly Internet use (Fisher's exact=9.59; p=0.02) and smart phone access (Fisher's exact=6.15; p=0.02). Computer Internet access was significantly associated with income (Fisher's exact=16.91; p<0.001). Logistic regression identified that computer Internet access was a significant predictor (odds ratio 9.9 (95% confidence interval: 1.7?58.8) of future portal use, controlling for smart phone use, health status, gender, and age. Conclusions: Among this highly educated but lower economic sample, computer Internet access and smart phone access were associated with past portal use and anticipated future use.